Comparison of the nutritional and fatty acid composition of the milk of four South American camelid species - Medina, Mirta Asunción (2018)
The nutritional value, whey protein and the fatty acid composition of the four South American Camelid's milk, vicuna (Vicugna vicugna), alpaca (Vicugna pacos), guanaco (Lama guanicoe) and llama (Lama glama) were evaluated and compared to old-world camelids. Samples were collected from healthy animals from the Northwest (llama, alpaca and vicuna) and Patagonia (guanaco) areas of Argentina. Milk gross composition of SAC showed a higher protein, lactose and lipid content than camel milk. Serum albumin and -lactalbumin were the dominant whey proteins, followed by IgG immunoglobulin. The fatty acid profile showed from 4:0 to 24:0 fatty acids, with a high level of conjugated fatty acid (CLA, 1.05-1.64 g/100 g FAME) and its precursor, vaccenic acid. Desaturase activity for C16 and CLA were quite similar between species, but significantly different for C14. Camelid milk showed a lower atherogenic index than ruminant milk. By the first time, a comparative study about the four species of South American camelid was carried out, contributing to the general knowledge of the physiology of new-world camelids. High nutritional quality was determined in the milk, allowing to be considered as a promising alternative food for humans in semi-arid region of South America.